Assessing Natural Low Temperature Conditions in Himalayan Region for Long-Term Storage of Seeds: Facilitating Cost-effective Conservation of Plant Genetic Resources - ANURUDH K. SINGH; S.K. JAIN; KALYANI SRINIVASAN; MANJU UPRETY; NARENDRA SINGH; B. RAUT; D.P. ATTREY; RAKESH SINGH (Seed Research, 2026)
Long-term conservation of plant genetic resources is commonly managed through storage of seeds in refrigerated chambers maintaining sub-zero temperatures, which is expensive. Hence, cost-effective long-term conservation is one of the research priorities. High altitude site, Khardung La at the height of 18,338 ft. in the Himalayan region with sub-zero temperatures for most part of the year, is explored for storage of seeds of 149 representative accessions in 47 major field and horticultural crops, belonging to various crop groups. The quality (germination) of stored seed was monitored at periodic intervals viz., one year, two years and four years. The results indicated that nearly all accessions were able to maintain their seed quality very close to their original values; suggesting that the seed material of diverse crop species can be cost-effectively stored for long-term duration under natural low temperature conditions prevailing in the Himalayan region.